Calibration of the numerical model of a stone masonry railway bridge based on experimentally identified modal parameters. (15th September 2016) - Costa, C.; Ribeiro, D.; Jorge, P.; Silva, R.; Arêde, A.; Calçada, R.
Highlights: 3D finite element modelling of a stone masonry arch bridge. Material model parameters based on experimental in-situ and lab testing. An ambient vibration test allowed the identification of the modal parameters. The calibration was performed using a genetic algorithm that proved good robustness. The optimized material parameters were bounded with experimentally obtained ones. Abstract: This paper focuses on the calibration of a numerical model of a stone masonry arch railway bridge using dynamic modal parameters estimated from an ambient vibration test. The developed 3D numerical model is based on the finite element method, featuring a realistic representation of the bridge structural components and materials. The calibration methodology relied on a genetic algorithm strategy which allowed estimating and updating numerical model parameters, particularly the elastic properties of materials. The validation of the updated bridge material properties' parameters was based on the results of material testing, on existing bridge design data and on observations resulting from in situ visual inspections.